(untitled) (International Seven Journal of Health Research, 2024)
Paliperidone is a safe and effective option for the treatment of schizophrenia, with long-acting oral or intramuscular administration. Its low hepatic metabolization and renal excretion minimize complications in patients with pre-existing liver disease, providing greater adherence and therapeutic efficacy. The current study is a literature review, with an active search for “Paliperidone” and “Schizophrenia” on national and international platforms. Twenty-one articles were analyzed in the PubMed and Scielo databases. Twenty-one articles were selected based on an evaluation of the title, abstract and relevance to the study. The period of publication ranged from 2007 to 2024, and all were organized in terms of title, authorship, year of publication and methodology used. The data shows the consistent efficacy of paliperidone in relieving schizophrenic symptoms, its safety and tolerability, highlighting its ability to improve patients’ quality of life. Although adverse events were observed, these were generally mild and did not compromise the continuity of treatment. In summary, the data support paliperidone as an effective and safe therapeutic option for schizophrenia, with the potential to improve patients’ clinical and psychosocial outcomes. Paliperidone is an effective and well-tolerated option for treating schizophrenia, with studies indicating improved patient compliance and clinical stability. Its low incidence of serious side effects increases long-term safety. This reduces relapse and hospitalization rates, improving quality of life.